Measurement of Victim Credibility in Child Sexual Assault Cases: A Systematic Review. (January 2019) - Voogt, Ashmyra; Klettke, Bianca; Crossman, Angela
While the concept of credibility seems like an intuitive one, research has indicated that there is no consistent definition of this construct and that credibility may, in fact, be multidimensional. This article is the first to review how the measurement of credibility in child sexual assault cases has been conducted, with the view to improve how credibility is psychometrically measured. Our findings indicate that the majority of experiments have been conducted in the United States (67%), have been based primarily on undergraduate students as participants (67%), and primarily investigated cases involving a male defendant and female victim (69%). Ultimately, among experiments investigating victim credibility, approximately 60% of all measures were based on a single item and 53% used materials not based on the testimony of the child. Moreover, credibility has been measured using a great variety of constructs such as believability, honesty, truthfulness, suggestibility, accuracy, and reliability. A more nuanced and consistent definition of credibility will be needed to facilitate meaningful applications of the research literature.